Non-Typhoid Salmonella Causes Food-borne Diseases: Its Prevention and Control - Engki Zelpina; S M Noor (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2020)
Non-typhoid Salmonella (NTS) is a pathogenic bacteria causing gastroenteritis in humans which is transmitted through animals and contaminated animal products with Salmonella typhimurium or Salmonella enteritidis. Many cases of NTS infection in humans have been reported in the world, however most people in Indonesian are generally more familiar with Salmonella typhoid, which is caused by Salmonella typhoid and Salmonella paratypoid. Gastroenteritis due to NTS infection seldom requires antimicrobial treatment. If there is no post-infectious complications such as septicemia, reactive arthritis or aortic aneurysm. Eggs, chicken meat, raw milk and other animal products contaminated with NTS are a source of transmission through food (food-borne pathogens). An estimated 1-3% of pets carry NTS without causing illness. Control of NTS infection is difficult because Salmonella is tolerant to environmental stresses, widely spread, resistant to several types of antibiotics and has the ability to adapt. The application of strict biosecurity on farms is conducted through surveillance and monitoring so that it can  prevent the contamination of livestock products and their derivatives, hence, it can prevent the transmission of NTS to humans. This paper provides information on NTS in animal and human prevention and control.